Nódulos tiroideos y predisposición al desarrollo de cáncer tiroideo. Hospital Provincial General Docente Riobamba 2018 - Badillo Pazmiño, Francisco Xavier (2019)
Introduction: Worldwide thyroid cancer (TC) has an approximate incidence of 9 cases per 100 000 inhabitants, the highest incidence is observed in women at 40 years. The presence of thyroid nodules is common and its importance resides in dismissing malignancy in them. Approximately 5% of clinically palpable thyroid nodules demonstrate malignancy. Objectives: To identify the correlation of patients with thyroid nodules and the appearance of thyroid cancer. Material and methods: This study is of a quantitative, descriptive, cross-sectional type. It investigated the entire population of patients with thyroid nodules who attended the external consultation of the HPGDR during 2018, obtaining a universe of 219 patients. Results: The highest prevalence rate of thyroid nodules is present in patients under 40 years old with a percentage of 30.59% of female sex corresponding to 92.69%. According to the TI-RADS scale, 52.05% belongs to TI-RADS 2 sonographic studies, followed in incidence by the TI-RADS 3 class with 28%. 54 patients were candidates for PAAF, this 72.22% was BETHESDA II, and 18.52% BETHESDA VI.Conclusions: There is a relationship between the appearance of thyroid nodules and the subsequent development of thyroid cancer with a 5% probability of occurrence.